2014
DOI: 10.1007/s00240-014-0724-6
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral wall thickness at the impacted ureteral stone site: a critical predictor for success rates after SWL

Abstract: The aim of the study was to determine the possible predictive value of certain patient- and stone-related factors on the stone-free rates and auxiliary procedures after extracorporeal shock wave lithotripsy in patients with impacted proximal ureteral calculi. A total of 111 patients (86 male, 25 females M/F: 3.44/1) with impacted proximal ureteral stones treated with shock wave lithotripsy were evaluated. Cases were retrieved from a departmental shock wave lithotripsy database. Variables analyzed included BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
3
51
0
1
Order By: Relevance
“…Additionally, the possible effect of UWT at the site of the stone as a predictive factor for final stone expulsion rates after MET has been evaluated in a recently published study, and UWT has been found to be a reliable predictor parameter [42] . Moreover, in their original study, Sarica et al [43] were able to show the predictive value of UWT on the SFR as well as additional procedure rates after SWL in ureteric stones with a cutoff value 3.55 mm over which additional procedure rates were found to be meaningfully high. Therefore, in this present study, we aimed to evaluate the possible predictive value of these stones as well as their anatomy-related parameters to predict the stone expulsion rates after MET in children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the possible effect of UWT at the site of the stone as a predictive factor for final stone expulsion rates after MET has been evaluated in a recently published study, and UWT has been found to be a reliable predictor parameter [42] . Moreover, in their original study, Sarica et al [43] were able to show the predictive value of UWT on the SFR as well as additional procedure rates after SWL in ureteric stones with a cutoff value 3.55 mm over which additional procedure rates were found to be meaningfully high. Therefore, in this present study, we aimed to evaluate the possible predictive value of these stones as well as their anatomy-related parameters to predict the stone expulsion rates after MET in children.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of colic pain seemed to be associated with hydronephrosis and a slightly delayed excretion of urine, possibly caused by the beginning of ureteral edema [9]. Obstructing impacted ureter stones may stay in the same position for a certain period of time and if not treated on time, the function of the affected kidney may face a progressive deterioration [18,19]. Therefore, ureteral stones in patients with colic pain, which are much less likely than in non-colic patients to be impacted stones, may be fragmented and passaged after treatment of SWL.…”
Section: Discussionmentioning
confidence: 99%
“…The rate for ureteral stones >10 mm decreases to 68 and 79% if treated by ESWL and URS, respectively [6] . In our study, similar to the literature, the success rate was found to be 81.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Nine hundred and twenty patients, 592 males (64%) and 328 females (36%), with an average age of 45 years (10-90 years) were included in the evaluation. Impacted ureteral stone was defined as calculi causing ureteral obstruction with lack of evident visualization beyond the stone on contrast graphics, remaining in the same position for more than 1 month and resulting in dilation in the collecting system [6] . All patients had kidney function tests, urinalysis, urine culture (when needed), kidney-ureter-bladder (KUB) radiography, CT or intravenous urography, and ultrasonography before surgery.…”
Section: Study Populationmentioning
confidence: 99%